2010
DOI: 10.1177/0040517510383620
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cotton and cotton trash components by Fourier transform near-infrared spectroscopy

Abstract: The high demand for cotton production worldwide has demonstrated the need for standardized classification of foreign matter present with cotton. Cotton trash can become comingled with fiber during the ginning and harvesting processes. The conventional instrumental method used to determine the amount of cotton trash present with cotton fiber, the high volume instrument (HVI), lacks specificity in the identification of individual trash components (leaf, etc.). Fourier transform near-infrared (FT-NIR) spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 10 publications
(17 reference statements)
0
34
0
Order By: Relevance
“…The development of an FT-IR spectral database yielded highly accuracte identification of cotton trash and foreign matter serving as a "proof of concept" of the utility of this instrumental method. Fortier and co-workers later compared their FT-IR results to that of this preliminary FT-IR study by Himmelsbach and co-workers (Fortier et al, 2010). The two studies yielded comparable results.…”
Section: Botanical and Synthetic Cotton Trashmentioning
confidence: 93%
See 1 more Smart Citation
“…The development of an FT-IR spectral database yielded highly accuracte identification of cotton trash and foreign matter serving as a "proof of concept" of the utility of this instrumental method. Fortier and co-workers later compared their FT-IR results to that of this preliminary FT-IR study by Himmelsbach and co-workers (Fortier et al, 2010). The two studies yielded comparable results.…”
Section: Botanical and Synthetic Cotton Trashmentioning
confidence: 93%
“…In terms of the cotton trash, there was considerable overlap throughout the entire spectral region with a defining peak over the spectral region of 1400 nm to 1500 nm which did not include a cotton peak. Even though cotton had distinctive spectral bands, the investigation was continued to gain non-overlapping spectral identity for all the trash components with a validation report showing no confused components (Fortier et al, 2010). Thus, the investigation was expanded to include different wavelength ranges and other preprocessing methods.…”
Section: Fourier-transform Near-infrared Spectroscopy Of Botanical Comentioning
confidence: 99%
“…The observation revealed the potential of visible/NIR technique in the precise and quantitative determination of total trash, leaf trash, and non-leaf trash components, but it also indicated the difficulty in the prediction of non-leaf trash components such as stem, hull, seed coat, and sand/soil. As a different approach, Fortier et al [14] reported NIR spectral feature of individual or pure plant parts and further for their identifications.…”
Section: Introductionmentioning
confidence: 99%
“…Fortier et al identified botanical trash using near-infrared spectroscopy [3]. By applying a subcategory between the hull and seed coat, a database composed of botanical trash including hull, leaf, seed coat, and stem was designed.…”
mentioning
confidence: 99%